Comparison of muscle activation levels between healthy individuals and persons who have undergone anterior cruciate ligament reconstruction during different phases of weight-bearing exercises - Harput, G.; Sebert Howard, J.; Mattacola, C. (Journal of Orthopaedic & Sports Physical Therapy, 2016)
Study Design: Cross-sectional, controlled laboratory study. Background: Quantification of muscular activation during different phases of functional activities is important to understand activation deficits in individuals who have undergone anterior cruciate ligament reconstruction (ACLR). Objectives: To compare activation levels of vastus medialis (VM), medial hamstrings (MH) and gluteus medius (GMed) muscles during the different phases of weight bearing tasks between individuals who had undergone ACLR and healthy controls. Methods: Surface electromyography was used to measure the activation levels of VM, MH and GMed muscles in 16 participants who had undergone ACLR (average time since surgery: 4 yrs) and 15 healthy participants during the reach and return phases of the star excursion balance test (SEBT) and the ascending and descending phases of a step down task (SDT). Repeated measures ANOVAs were performed to determine whether muscle activation levels differed between groups during different phases of the tasks. Results: There were significant group by phase interactions for the GMed during both SEBT and the SDT. GMed activation was lower for the ACLR group during the return phase of the posteromedial direction of the SEBT compared to the control group (P = .03). During the SDT, GMed activation was higher for the ACLR group during the ascending phase than descending phase (P<.001), while the control group showed no difference between phases (P = .707). Conclusion: Individuals who have undergone ACLR have similar VM and MH activation compared to healthy individuals during different phases of the SDT and SEBT. However, phase differences for GMed activity and decreased GMed activity relative to healthy individuals were observed among ACLR participants